Factors Affecting Reluctance to Malaysian Adults’ COVID-19 Vaccine Booster Doses - Nadhiah Abd Rahman; Hemaloshinee Vasudevan; Heinko Dona Madon; Noorseha Ayob (Buletin Ilmu Kebidanan dan Keperawatan, 2026)
This study examines the factors that affect COVID-19 booster vaccine hesitancy among Malaysian adults, utilizing the 5C Vaccination Decision-Making Framework and a modified Theory of Planned Behavior (TPB). Malaysia's rollout of booster doses faces significant hesitancy, indicating a need to explore the underlying reasons. The research identifies key physical and psychological determinants influencing vaccine intentions, particularly emphasizing confidence, constraints, complacency, calculation, and collective responsibility, while highlighting the mediating role of attitude. Data from 100 Malaysian adults were collected through a cross-sectional web-based survey and analyzed using SPSS and structural equation modeling (SEM) with SmartPLS. The findings indicate that confidence in vaccine efficacy is a strong predictor of positive attitudes and intentions, while constraints have a moderate influence, and complacency exerts a negative impact on attitudes. Calculation does not significantly relate to attitudes, indicating that factual information has limited effects in the context of misinformation and trust issues. This research underscores the mediating influence of attitudes on the interplay between confidence, constraints, complacency, calculation, and collective responsibility concerning vaccination intentions, highlighting the importance of promoting positive vaccine perceptions. The study recommends comprehensive strategies to enhance confidence, reduce barriers, combat complacency, provide accurate information, and promote collective responsibility to improve COVID-19 booster vaccine uptake.